Designing 2d Assets As Digital Promotional Media For Batak Mandailing Culture - Hanafi Muhammad Nurhadi; Mario Mario; Pebriyanto Pebriyanto (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
Designing 2D Assets as Digital Promotional Media for Batak Mandailing Traditional Clothing. This study is motivated by the declining appreciation of younger generations for local culture amid globalization and the rapid development of digital media. The research object focuses on Batak Mandailing traditional clothing, visualized in the form of 2D illustration assets, including men’s and women’s traditional attire and supporting elements such as ulos, bulang, colors, and traditional accessories. This study aims to design representative and communicative 2D visual assets as digital promotional media as well as a means of cultural education. The method used is descriptive qualitative research with a visual design approach through the stages of data collection, visual analysis, sketching, digitalization, coloring, and finalization. The results show that 2D illustrations in a semi-realistic style can visually represent Mandailing traditional clothing without eliminating its symbolic values. In addition, this visualization can enhance aesthetic appeal, making it more acceptable to audiences, especially younger generations. In conclusion, the design of 2D illustration assets for Batak Mandailing traditional clothing can serve as an effective digital promotional medium as well as a visual educational tool to support the preservation and strengthening of local cultural identity in the digital era.